Thrombin-induced platelet activation via PAR4: pivotal role for exosite II - Boknäs, Niklas; Faxälv, Lars; Centellas, Daniel Sanchez; Wallstedt, Maria; Ramström, Sofia; Grenegård, Magnus; Lindahl, Tomas L. (Thrombosis and Haemostasis, 2014)
Thrombin-induced platelet activation via PAR1 and PAR4 is an important event in haemostasis. Although the underlying mechanisms responsible for ensuring efficient PAR1 activation by thrombin have been extensively studied, the potential involvement of recognitions sites outside the active site of the protease in thrombin-induced PAR4 activation is largely unknown. In this study, we developed a new assay to assess the importance of exosite I and II for PAR4 activation with α- and γ-thrombin. Surprisingly, we found that exosite II is critical for activation of PAR4. We also show that this dependency on exosite II likely represents a new mechanism, as it is unaffected by blockage of the previously known interaction between thrombin and glycoprotein Ibα.